Rapid electrical impedance detection of sickle cell vaso-occlusion in microfluidic device. - Qiang, Yuhao; Dieujuste, Darryl; Liu, Jia; Alvarez, Ofelia; Du, E (Biomedical Microdevices, 2023)
Sickle cell disease is characterized by painful vaso-occlusive crises, in which poorly deformable sickle cells play an important role in the complex vascular obstruction process. Existing techniques are mainly based on optical microscopy and video processing of sickle blood flow under normoxic condition, for measuring vaso-occlusion by a small fraction of dense sickle cells of intrinsic rigidity but not the vaso-occlusion by the rigid, sickled cells due to deoxygenation. Thus, these techniques are not suitable for rapid, point-of-care testing. Here, we integrate electrical impedance sensing and Polydimethylsiloxane-microvascular mimics with controlled oxygen level into a single microfluidic chip, for quantification of vaso-occlusion by rigid, sickled cells within 1 min. Electrical impedance measurements provided a label-free, real-time detection of different sickle cell flow behaviors, including steady flow, vaso-occlusion, and flow recovery in response to the deoxygenation-reoxygenation process that are validated by microscopic videos. Sensitivity of the real part and imaginary part of the impedance signals to the blood flow conditions in both natural sickle cell blood and simulants at four electrical frequencies (10, 50, 100, and 500 kHz) are compared. The results show that the sensitivity of the sensor in detection of vaso-occlusion decreases as electrical frequency increases, while the higher frequencies are preferable in measurement of steady flow behavior. Additional testing using sickle cell simulants, chemically crosslinked normal red blood cells, shows same high sensitivity in detection of vaso-occlusion as sickle cell vaso-occlusion under deoxygenation. This work enables point-of-care testing potentials in rapid, accurate detection of steady flow and sickle cell vaso-occlusion from microliter volume blood specimens. Quantification of sickle cell rheology in response to hypoxia, may provide useful indications for not only the kinetics of cell sickling, but also the altered hemodynamics as obseved at the microcirculatory level.